A lithium metal negative electrode sheet with a self-repairing molecular crystal protective layer, a preparation method and applications thereof

CN122991965APending Publication Date: 2026-10-27XIDIAN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611409930.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-11
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0007]为了克服上述现有技术的不足,本发明的目的在于提供一种具有自修复分子晶体保护层的锂金属负极极片、制备方法及其应用,通过利用Li(FSA)(SN)2分子晶体的低熔点和高锂离子电导率特性,将其加热熔融后直接涂覆在锂金属表面,冷却成型后形成一层致密、离子导电且化学/电化学稳定的物理屏障,解决锂金属与硫化物/卤化物固态电解质之间界面稳定性差的问题

Benefits of technology

1、本发明针对现有技术中硫化物、卤化物电解质固态锂电池在负极界面优化方面存在的问题,提供了一种简单有效的界面保护层构筑方法,利用Li(FSA)(SN)2分子晶体低熔点的特性,通过一步无溶剂、热熔融的绿色制备工艺,先将Li(FSA)(SN)2分子晶体在60-80°C范围内加热形成熔融态液体,然后在加热的锂金属负极极片表面进行物理涂覆,待涂覆完成后降至室温,使得Li(FSA)(SN)2分子晶体再次结晶,在锂金属负极表面构筑分子晶体保护层。该分子晶体保护层具有优异的锂离子传导能力(离子电导率达1.1×10-4S·cm-1,活化能仅10.19 kJ·mol-1),且对锂金属负极和固态电解质均具有良好的化学/电化学稳定性,在热熔融涂覆工艺下能够在锂金属负极表面形成紧密接触,通过自身晶体结构的机械性能物理阻隔锂金属负极与固态电解质的直接接触,从而隔绝两者间的化学/电化学副反应并抑制锂枝晶的生长,与此同时,分子晶体保护层为锂离子提供快速传输通道,显著降低锂金属负极与固态电解质两者间的界面阻抗,最终有效降低锂金属由于界面副反应造成的不可逆损失,进而提高电池的能量密度、能量效率和循环性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

A lithium metal negative electrode sheet with a self-repairing molecular crystal protective layer, a preparation method and applications thereof, utilize a lithium bis(fluorosulfonyl)imide butanedinitrile (Li(FSA)(SN)2) organic molecular crystal with high lithium ion conductivity and thermoplasticity as a protective layer material, the material utilizes its low melting point characteristic (about 60°C), through heating and melting, is uniformly coated on the surface of lithium metal, and after cooling, a dense protective film is formed, the molecular crystal protective layer can not only physically block the direct contact of lithium metal and solid-state electrolyte, inhibit chemical / electrochemical side reactions and lithium dendrite growth, but also provide an efficient lithium ion transmission channel (ion conductivity reaches 1.1*10 ‑4 S cm ‑1 ) at the interface; the present application has simple process, mild conditions and strong controllability, and can significantly improve the interface stability and cycle performance of the all-solid-state battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of new energy battery materials and all-solid-state battery technology, and specifically relates to a lithium metal anode sheet with a self-healing molecular crystal protective layer, its preparation method and its application. Background Technology

[0002] All-solid-state lithium batteries, constructed using sulfide or halide inorganic solid-state electrolytes, are considered strong contenders for next-generation energy storage technologies due to their high safety and high energy density potential. Lithium metal anodes, with their extremely high theoretical specific capacity and lowest electrochemical potential, are ideal for achieving high energy density. However, directly matching lithium metal anodes with sulfide / halide solid-state electrolytes presents significant interfacial challenges. On one hand, lithium metal is chemically reactive and readily reacts with sulfide (such as Li3PS4) or halide electrolytes, generating high-resistivity byproduct layers (such as Li2S, LiCl, Li2O, etc.), severely hindering lithium-ion transport. On the other hand, poor interfacial contact and uneven local current density can induce lithium dendrite growth, leading to battery short circuits and rapid performance degradation.

[0003] To address these issues, researchers have developed various interface engineering strategies, such as introducing artificial protective layers (e.g., Al2O3, LiF, polymers) onto the lithium metal surface. However, existing methods have limitations: physical vapor deposition and atomic layer deposition processes are complex and costly; some polymer protective layers exhibit low room-temperature ionic conductivity, increasing interfacial impedance; while alloy anodes (e.g., Li-In, Li-Sn) can improve interfacial kinetics, they sacrifice some specific capacity and increase the anode potential; and elemental doping or surface coating of solid electrolytes is complex and difficult to control precisely. Therefore, developing a novel protective layer material that is easy to prepare, has high ionic conductivity, good affinity with lithium metal, and also possesses mechanical properties is crucial.

[0004] In recent years, lithium-ion conductors based on organic molecular crystals have attracted attention. In particular, the Li(FSA)(SN)2 molecular crystal formed from lithium bis(fluorosulfonyl)imide and succinate has been reported to possess high lithium-ion conductivity (1.1 × 10⁻⁶ at 30°C). -4 Scm -1 1.1 × 10 at -20°C -5 S cm -1 ) and low activation energy (28 kJ mol) -1 It also exhibits a low melting point of approximately 60°C (see: Nano Lett. 2020, 20, 8200-8204). This material, combining high ionic conductivity with thermoplasticity, offers unprecedented opportunities for use as a processable protective layer for lithium metal anodes.

[0005] Patent application CN109167063A discloses a lithium metal anode protected by an artificial solid electrolyte interface layer and its preparation method. The method involves coating a mixed solution of alginic acid and lithium alginate onto the surface of a lithium metal sheet and drying it to form a dense and tough artificial solid electrolyte interface layer. Although this method can suppress lithium dendrites and improve cycle performance to a certain extent, it inevitably has the following problems due to its solution coating process: (1) the coating is prone to shrinkage and cracking during the solvent evaporation and drying process, making it difficult to form a completely dense and defect-free film; (2) solvent residue may contaminate the lithium metal interface and affect the interface purity; (3) the process involves multiple steps such as solution preparation, coating, and drying, which is cumbersome and has poor repeatability; (4) this technology is mainly for liquid electrolyte systems and has limited applicability in all-solid-state batteries.

[0006] Patent application CN113140785A discloses a modified solid electrolyte, its preparation method, and its application. The method involves depositing a lithium metal layer on the surface of a solid electrolyte using high-vacuum thermal evaporation, followed by in-situ nitriding with high-purity nitrogen to generate a Li3N protective layer, and finally densification by isostatic pressing. While this method utilizes the high ionic conductivity and low electronic conductivity of Li3N to achieve interface modification, its technical route has the following limitations: (1) It requires high-vacuum thermal evaporation coating or magnetron sputtering equipment, resulting in high process costs and difficulty in achieving large-area continuous production; (2) It requires additional nitriding and isostatic pressing, involving numerous steps and high energy consumption; (3) Preparing the protective layer on the surface of the solid electrolyte rather than the lithium metal anode surface does not directly suppress interfacial side reactions on the lithium metal side; (4) Voids easily form between the in-situ generated Li3N layer and the solid electrolyte, requiring additional cold pressing for densification, increasing process complexity and interfacial uncertainty. Summary of the Invention

[0007] To overcome the shortcomings of the prior art, the present invention aims to provide a lithium metal anode sheet with a self-healing molecular crystal protective layer, its preparation method, and its application. By utilizing the low melting point and high lithium-ion conductivity of Li(FSA)(SN)2 molecular crystal, it is heated and melted and then directly coated onto the surface of lithium metal. After cooling and forming, a dense, ionicly conductive, and chemically / electrochemically stable physical barrier is formed, solving the problem of poor interfacial stability between lithium metal and sulfide / halide solid electrolytes.

[0008] To achieve the above objectives, the technical solution adopted by the present invention is as follows: A lithium metal anode electrode with a self-healing molecular crystal protective layer, wherein the molecular crystal protective layer is attached to the surface of the lithium metal anode electrode and the material is lithium bis(fluorosulfonyl)imide-succinate organic molecular crystal with the chemical formula Li{N(SO2F)2}-(NCCH2CH2CN)2.

[0009] A method for preparing a lithium metal anode sheet with a self-healing molecular crystal protective layer includes the following steps: Step 1: Under an inert atmosphere, lithium bis(fluorosulfonyl)imide (LiFSA) and succinate (SN) raw materials mixed in a molar ratio of 1:2 are heated and stirred at 60-80°C to form a colorless and transparent molten Li(FSA)(SN)2 liquid. Step 2: Spread the lithium metal anode sheet evenly and heat it. Control the heating temperature at 60-80°C. Coat the surface of the heated lithium metal anode sheet with the molten Li(FSA)(SN)2 liquid obtained in Step 1 evenly. Step 3: Heat and hold the lithium metal anode sheet coated with molten Li(FSA)(SN)2 liquid for 5 to 30 minutes to completely melt the molecular crystal Li(FSA)(SN)2 and further spread it evenly on the surface of the lithium metal anode sheet to form a dense liquid film. Step 4: Cool the temperature to room temperature to allow the liquid film to cool and solidify on the surface of the lithium metal anode sheet, forming a continuous and dense Li(FSA)(SN)2 molecular crystal protective layer, thus obtaining a lithium metal anode sheet with a self-healing molecular crystal protective layer.

[0010] In step 2, the coating method includes any one of drip coating, scraping coating or immersion coating. The amount of Li(FSA)(SN)2 molten liquid is calculated according to the target thickness. The thickness of the molecular crystal protective layer after coating is controlled at 5~10 µm. The lithium metal negative electrode sheet is in the shape of a lithium foil, a lithium sheet, or a lithium film deposited on a current collector.

[0011] In step 3, the heating and heat preservation temperature is 60-80°C; In step 2 or 3, the heating method is hot plate heating, oven heating or infrared heating; wherein, hot plate heating uses a small constant temperature heating table, and infrared heating uses infrared lamps.

[0012] When the lithium metal negative electrode sheet with the self-healing molecular crystal protective layer is subjected to external pressure and local cracks appear, the negative electrode sheet is subjected to short-term heating treatment at 80°C to remelt the failed protective layer and allow it to penetrate into the crack again. After cooling, the interface self-healing is achieved.

[0013] The present invention further provides an application of the above lithium metal negative electrode sheet with a self-healing molecular crystal protective layer in an all-solid-state lithium metal battery. The all-solid-state lithium metal battery includes a positive electrode active material, solid electrolyte powder, and the above-described lithium metal negative electrode sheet with a self-healing molecular crystal protective layer, and the assembly steps of the all-solid-state lithium metal battery include: Step 5: mechanically mix the positive electrode active material, solid electrolyte powder and conductive agent in a certain proportion to prepare a composite positive electrode powder; Step 6: stack the composite positive electrode powder, the solid electrolyte powder, and the lithium metal negative electrode sheet with a self-healing molecular crystal protective layer in sequence, and perform tableting assembly under an inert atmosphere to obtain the all-solid-state lithium metal battery.

[0014] In the step 5, the solid electrolyte is a sulfide solid electrolyte or a halide solid electrolyte; The sulfide solid electrolyte includes: (1) Glass-type electrolytes xLi2S-(100-x)P2S5 (0<x<100), Li2S–SiS2–Li4MO4, where M is one or more of Si, Ge and P in any ratio; (2) Argyrodite-type electrolytes Li6PS5X, Li7PS6, Li 5.5 PS 4.5 X 1.5 , where X is one or more of Cl, Br and I in any ratio; (3) Thio-LISICON-type electrolytes Li x M 1-y M’ y S4 (0≤y<1, 2≤x≤5), where M is one or more of Sn, Ge and Si in any ratio, and M' is one or more of P, Al, Zn, Ga, Sb and As in any ratio; (4) Lithium germanium phosphorus sulfur-type electrolytes Li 11–x M 2–x P 1+x S 12 (0<x<2), Li7Ge3PS 12 , Li 11 AlP2S 12 , where M is one or more of Ge, Sn and Si in any ratio; The halide solid electrolyte includes: (1) Li2MCl4, wherein M is one or two of Mn or Zn in any proportion; (2) LiMX4, wherein M is one or more of Yb or Al or In in any proportion, and X is one or more of F or Cl or Br or I in any proportion; (3) LiMXCl4, wherein M is one or more of Ta or Nb or Sb or Ti or Zr or Hf or Sn in any proportion, and X is one or more of O or F or Cl in any proportion; (4) Li3MX6, wherein M is one or more of Y or In or Er or Ho or Sc or Sm or Nb or Ga or Bi or Lu or Tm or Dy or Tb in any proportion, and X is one or more of Cl or Br or I in any proportion; (5) Li6MX8, wherein M is one or more of Co or V or Fe in any proportion, and X is one or more of Cl or Br or I in any proportion; (6) Li2MX6, wherein M is one or more of Zr or Ti or Sn or Ge in any proportion, and X is one or more of Cl or Br or I in any proportion.

[0015] In step 5, the positive electrode active material is selected from lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2), and lithium nickel manganese cobalt oxide (LiNiO2). 1-x-y Co x Mn y O2, 0 < 1 - xy ≤ 1), lithium nickel cobalt aluminum oxide (LiNi 1-x-y Co x Al y O2, 0 < 1 - xy ≤ 1), LiNi 0.5 Mn 1.5 O4, LiMn2O4, lithium-rich manganese-based cathode (xLi2MnO3·(1-x)LiMO2, where M is one or more of Mn, Co, or Ni in any proportion, 0<1-x≤1), and lithium iron phosphate (LiFePO4) in any proportion; In step 5, the conductive agent is one or more of Ketjen Black, acetylene black, vapor-grown carbon fiber (VGCF), and carbon nanotubes (CNT) in any proportion.

[0016] In step 5, the mass ratio of the positive electrode active material, solid electrolyte powder and conductive agent is (60–80):(38–18):2.

[0017] In step 6, the pressure for tablet assembly is 50~500 MPa, and the holding time is 10~60 seconds.

[0018] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. This invention addresses the problems existing in the optimization of the negative electrode interface in sulfide and halide electrolyte solid-state lithium batteries, providing a simple and effective method for constructing an interface protective layer. Utilizing the low melting point of Li(FSA)(SN)2 molecular crystals, a one-step solvent-free, hot-melting green preparation process is employed. First, Li(FSA)(SN)2 molecular crystals are heated to a molten state within the range of 60-80°C. Then, a physical coating is applied to the surface of the heated lithium metal negative electrode. After coating, the mixture is cooled to room temperature, allowing the Li(FSA)(SN)2 molecular crystals to recrystallize, thus constructing a molecular crystal protective layer on the lithium metal negative electrode surface. This molecular crystal protective layer exhibits excellent lithium-ion conductivity (ionic conductivity reaching 1.1 × 10⁻⁶). -4 S·cm -1 The activation energy is only 10.19 kJ·mol⁻¹ -1 Furthermore, it exhibits excellent chemical / electrochemical stability for both the lithium metal anode and the solid electrolyte. Under the hot-melt coating process, it can form a tight contact on the surface of the lithium metal anode. Through the mechanical properties of its own crystal structure, it physically blocks the direct contact between the lithium metal anode and the solid electrolyte, thereby isolating the chemical / electrochemical side reactions between the two and inhibiting the growth of lithium dendrites. At the same time, the molecular crystal protective layer provides a fast transport channel for lithium ions, significantly reducing the interfacial impedance between the lithium metal anode and the solid electrolyte. Ultimately, it effectively reduces the irreversible loss of lithium metal caused by interfacial side reactions, thereby improving the energy density, energy efficiency and cycle performance of the battery.

[0019] 2. Addressing the problem that existing interface protective layers, such as organic and inorganic protective layers, lack sufficient mechanical strength or have high rigidity, making self-repair difficult after damage, the molecular crystal protective layer prepared in this invention possesses self-healing capabilities. Utilizing the reversible melting-solidification process of the Li(FSA)(SN)2 molecular crystal protective layer, by subjecting the molecular crystal protective layer with localized cracks caused by uneven stress to a short-term heating treatment at 80°C, the molecular crystal protective layer melts and penetrates into the cracks. After cooling, it recrystallizes back into a molecular crystal protective layer, thereby achieving interface self-healing. If the protective layer is damaged during use, it can be self-repaired through gentle reheating, exhibiting good process tolerance and interface durability.

[0020] 3. In view of the problems of solvent residue, drying shrinkage and complicated process in the solution coating method used in existing interface modification technology, the present invention does not require any solvent or binder. It directly utilizes the low melting point of Li(FSA)(SN)2 molecular crystal at about 60°C-80°C for molten liquid phase coating, avoiding coating shrinkage and cracking and interface contamination caused by solvent evaporation. It can form a more uniform, dense and defect-free thin film protective layer on the lithium metal surface, greatly simplifying the process and significantly improving repeatability and controllability.

[0021] 4. In view of the problems of high equipment cost, numerous steps and high energy consumption in the existing interface modification technology, such as high vacuum deposition, nitriding treatment and isostatic pressing, the present invention can achieve melting, spreading and cooling solidification by gentle heating at 60~80°C under normal pressure and inert atmosphere. It does not require high vacuum coating equipment, nitriding reaction device and high pressure cold pressing equipment. The preparation conditions are mild, the cost is significantly reduced, and it is easy to realize large-area continuous production, which has good prospects for large-scale application. Attached Figure Description

[0022] Figure 1 These are photographs of the preparation and heating-cooling cycle of the Li(FSA)(SN)2 molecular crystal material in this invention; wherein, Figure 1 (a) in the figure represents the material preparation process. Figure 1 (b) in the figure represents the heating-cooling cycle of the material.

[0023] Figure 2 These are photographs of the actual lithium metal anode prepared with a Li(FSA)(SN)2 protective layer in this invention.

[0024] Figure 3 This is a scanning electron microscope (SEM) image of the cross-section of a lithium metal anode coated with a Li(FSA)(SN)2 protective layer in Embodiment 1 of the present invention.

[0025] Figure 4 This is a photograph of the self-healing effect of the molecular crystal protective layer under heating in an embodiment of the present invention.

[0026] Figure 5 This is a graph showing the test data of the lithium-ion conductivity of the Li(FSA)(SN)2 molecular crystal material in this invention; wherein, Figure 5 (a) in the diagram is a variable-temperature AC impedance diagram. Figure 5 (b) in the figure is the Arrhenius plot of ionic conductivity at varying temperatures.

[0027] Figure 6 This is a comparison graph showing the critical current density (CCD) at room temperature of the all-solid-state lithium metal symmetric battery assembled in Example 1 and Comparative Example 1 of the present invention. Figure 6 Image (a) in the image is a room-temperature CCD image of the all-solid-state lithium metal symmetric battery of Example 1. Figure 6 (b) is a room temperature CCD image of the all-solid-state lithium metal symmetric battery of Comparative Example 1.

[0028] Figure 7 This is a comparison chart of the charge-discharge cycle performance of the all-solid-state lithium metal symmetric battery assembled in Example 1 and Comparative Example 1 under constant current density.

[0029] Figure 8This is a comparison chart of the cycle performance of the all-solid-state lithium metal batteries assembled in Example 1 and Comparative Example 2 of the present invention.

[0030] Figure 9 This is a graph showing the impedance change of the battery before and after repair in Embodiment 1 of the present invention. Detailed Implementation

[0031] The present invention will be further described in detail below with reference to specific embodiments and accompanying drawings. The following embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Experimental methods not specifically described in the embodiments are generally performed under conventional conditions.

[0032] This invention provides a lithium metal anode sheet with a self-healing molecular crystal protective layer, its preparation method, and its application in all-solid-state batteries. By utilizing the low melting point of molecular crystal Li(FSA)(SN)2 at 60-80°C, a uniform, dense, and ionically conductive protective film is constructed on the surface of lithium metal, thereby solving the problem of interfacial instability between lithium metal and sulfide / halide solid electrolytes in all-solid-state lithium metal batteries.

[0033] A lithium metal anode electrode with a self-healing molecular crystal protective layer, wherein the molecular crystal protective layer is attached to the surface of the lithium metal anode electrode and its material is lithium bis(fluorosulfonyl)imide-succinate organic molecular crystal with the chemical formula Li{N(SO2F)2}-(NCCH2CH2CN)2, abbreviated as Li(FSA)(SN)2.

[0034] A method for preparing a lithium metal anode sheet with a self-healing molecular crystal protective layer includes the following steps: Step 1: Under an inert atmosphere (water and oxygen content both below 0.1 ppm), weigh lithium bis(fluorosulfonyl)imide (LiFSA) and succinate (SN) at a molar ratio of 1:2 and mix them in a reaction flask. Heat and stir the mixture at 60-80°C until a colorless, transparent, molten Li(FSA)(SN)2 liquid is formed. In some embodiments, the inert atmosphere in step 1 includes argon and nitrogen.

[0035] Step 2: Spread the lithium metal anode sheet evenly and heat it. Control the heating temperature at 60-80°C. Coat the surface of the heated lithium metal anode sheet with the molten Li(FSA)(SN)2 liquid obtained in Step 1 evenly. The temperature of the heating stage is controlled at 60-80°C, which exceeds the melting point of the Li(FSA)(SN)2 molecular crystal. This ensures that Li(FSA)(SN)2 remains in a liquid flow state and spreads smoothly onto the surface of the lithium metal anode sheet during the coating process through shear force.

[0036] In some embodiments, the coating method in step 2 includes any one of drip coating, scraping coating, or immersion coating; the amount of Li(FSA)(SN)2 molten liquid is calculated according to the target thickness, and the molecular crystal protective layer after coating is controlled at 5~10 μm.

[0037] In some embodiments, in step 2, the lithium metal negative electrode sheet is in the shape of a lithium foil, a lithium sheet, or a lithium film deposited on a current collector.

[0038] Step 3: Heat and hold the lithium metal anode sheet coated with molten Li(FSA)(SN)2 liquid for 5 to 30 minutes to completely melt the molecular crystal Li(FSA)(SN)2 and further spread it evenly on the surface of the lithium metal anode sheet to form a dense liquid film. In some embodiments, the heating and heat preservation temperature in step 3 is 60-80°C.

[0039] In some embodiments, the heating and heat preservation method in step 3 is hot plate heating, oven heating, or infrared heating. Specifically, hot plate heating uses a small constant-temperature heating table, and infrared heating uses infrared lamps.

[0040] During the heat preservation process, bubbles or defects caused by uneven coating will be eliminated under gravity. The molten Li(FSA)(SN)2 liquid can then be evenly spread on the surface of the lithium metal anode sheet, ensuring full contact with it. Furthermore, this step fully utilizes the low melting point of the Li(FSA)(SN)2 molecular crystal for molten liquid phase coating, avoiding coating shrinkage and cracking caused by solvent evaporation and interface contamination. The interface modification process is significantly simplified, repeatability and controllability are greatly improved, and the mild and simple preparation conditions can significantly reduce costs, enabling large-scale application.

[0041] Step 4: Cool the temperature to room temperature to allow the liquid film to cool and solidify on the surface of the lithium metal anode sheet, forming a continuous and dense Li(FSA)(SN)2 molecular crystal protective layer, thus obtaining a lithium metal anode sheet with a self-healing molecular crystal protective layer.

[0042] Thanks to the stable coordination structure and high reduction stability of the Li(FSA)(SN)2 molecular crystal, the interface between the molecular crystal and the lithium metal anode can be maintained intact in the absence of an external electric field. At the same time, as an ion conductor, the Li(FSA)(SN)2 molecular crystal can effectively maintain ion conduction at its interface with the lithium metal anode.

[0043] This embodiment provides a method for self-healing the protective layer of a lithium metal anode electrode with a self-healing molecular crystal protective layer, including: When the lithium metal negative electrode sheet with the self-healing molecular crystal protective layer is applied with external pressure and local cracks appear, the negative electrode sheet is subjected to a short-time heat treatment at 80°C, so that the failed protective layer re-melts and penetrates into the cracks again, and the interface self-healing is achieved after cooling.

[0044] The Li(FSA)(SN)₂ molecular crystal protective layer of the present invention has the reversible melting-solidification characteristic, and the self-healing of the protective layer damaged by repeated mechanical stress and strain during use is realized by mild reheating. Compared with the situation that traditional organic protective layers and inorganic protective layers are difficult to self-heal after damage due to insufficient mechanical strength or high rigidity, this step enables the lithium metal negative electrode interface protective layer to have good process fault tolerance and interface durability.

[0045] The present invention also provides an application of the above-mentioned lithium metal negative electrode sheet with a self-healing molecular crystal protective layer in an all-solid-state lithium metal battery. The all-solid-state lithium metal battery includes a positive electrode active material, solid electrolyte powder and the above-mentioned lithium metal negative electrode sheet with a self-healing molecular crystal protective layer, and the assembly steps of the all-solid-state lithium metal battery include: Step 5: mechanically mix the positive electrode active material, solid electrolyte powder and conductive agent in a certain proportion to prepare a composite positive electrode powder; Step 6: stack the composite positive electrode powder, the solid electrolyte powder and the lithium metal negative electrode sheet with the self-healing molecular crystal protective layer in sequence, and perform tableting assembly under an inert atmosphere to obtain the all-solid-state lithium metal battery.

[0046] The Li(FSA)(SN)₂ molecular crystal protective layer has good chemical / electrochemical stability to the solid electrolyte, and physically blocks the direct contact between the lithium metal negative electrode and the solid electrolyte through the mechanical properties of its own crystal structure, thereby isolating the chemical / electrochemical side reactions between the two and inhibiting the growth of lithium dendrites. At the same time, as an ionic conductor, the Li(FSA)(SN)₂ molecular crystal can effectively buffer the chemical potential difference between lithium metal and the solid electrolyte, inhibit the formation of an unfavorable space charge layer, and further reduce the interface impedance.

[0047] In some embodiments, the sulfide solid electrolyte of the present invention includes but is not limited to: (1) glass-type electrolyte xLi₂S-(100-x)P₂S₅ (0<x<100), Li₂S–SiS₂–Li₄MO₄, wherein M is one or more of Si, Ge or P in any proportion; (2) argyrodite-type electrolyte Li₆PS₅X, Li₇PS₆, Li 5.5 PS 4.5 X 1.5 , wherein X is one or more of Cl, Br or I in any proportion; (3) sulfide crystalline lithium superionic conductor-type electrolyte Lix M 1-y M' y S4 (0≤y<1, 2≤x≤5), where M is one or more of Sn, Ge or Si in any proportion, and M' is one or more of P, Al, Zn or Ga, Sb or As in any proportion; (4) Lithium-germanium-phosphorus-sulfur electrolyte Li 11–x M 2–x P 1+x S 12 (0) <x<2),Li7Ge3PS 12 Li 11 AlP2S 12 , where M is one or more of Ge, Sn or Si in any proportion.

[0048] In some embodiments, the halide solid electrolyte of the present invention includes, but is not limited to: (1) Li₂MCl₄, wherein M is one or two of Mn or Zn in any proportion; (2) LiMX₄, wherein M is one or more of Yb, Al or In in any proportion, and X is one or more of F, Cl, Br or I in any proportion; (3) LiMXCl₄, wherein M is one or more of Ta, Nb, Sb or Ti, Zr or Hf or Sn in any proportion, and X is one or more of O, F or Cl in any proportion; (4) Li 3MX6, wherein M is one or more of Y, In, Er, Ho, Sc, Sm, Nb, Ga, Bi, Lu, Tm, Dy, or Tb in any proportion, and X is one or more of Cl, Br, or I in any proportion; (5) Li6MX8, wherein M is one or more of Co, V, or Fe in any proportion, and X is one or more of Cl, Br, or I in any proportion; (6) Li2MX6, wherein M is one or more of Zr, Ti, Sn, or Ge in any proportion, and X is one or more of Cl, Br, or I in any proportion.

[0049] In some embodiments, the positive electrode active material is selected from lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2), and lithium nickel manganese cobalt oxide (LiNiO2). 1-x-y Co x Mn y O2, 0 < 1 - xy ≤ 1), lithium nickel cobalt aluminum oxide (LiNi 1-x-y Co x Al y O2, 0 < 1 - xy ≤ 1), LiNi 0.5 Mn 1.5O4, LiMn2O4, lithium-rich manganese-based cathode (xLi2MnO3·(1-x)LiMO2, where M is one or more of Mn, Co, or Ni in any proportion, 0<1-x≤1), and lithium iron phosphate (LiFePO4) in any proportion.

[0050] In some embodiments, the conductive agent is one or more of Ketjen Black, acetylene black, vapor-grown carbon fiber (VGCF), and carbon nanotubes (CNTs) in any proportion.

[0051] In some embodiments, the preferred mass ratio of the positive electrode active material, solid electrolyte powder and conductive agent is (60–80):(38–18):2.

[0052] In some embodiments, the pressure for tablet assembly in step 6 is 50~500 MPa, and the holding time is 10~60 seconds.

[0053] Example 1 A method for preparing a lithium metal anode sheet with a self-healing molecular crystal protective layer includes the following steps: Step 1: In a glove box filled with argon (water and oxygen content both below 0.1 ppm), weigh the dried lithium bis(fluorosulfonyl)imide (LiFSA, 5.04 mmol, 0.9428 g) and succinate (SN, 10.0 mmol, 0.8024 g), add them to the reaction flask, seal it, transfer it to a heating platform, heat it to 80°C and stir it at a constant temperature until all solids are completely melted to form a colorless and transparent molten Li(FSA)(SN)2 liquid; The liquid, upon cooling to room temperature, becomes white Li(FSA)(SN)2 molecular crystals (such as...). Figure 1 As shown in (a)), DSC testing shows its melting point is 59.5°C, and it turns back into a colorless liquid after heating to 80°C (as shown in (a)). Figure 1 (as shown in (b)).

[0054] Step 2: In an argon glove box (with water and oxygen content below 0.1 ppm), take a lithium foil with a thickness of 50 µm, gently wipe the surface with a non-woven cloth, and spread it evenly on the surface of the heating table. The heating temperature is controlled at 80°C. The molten Li(FSA)(SN)2 liquid obtained in Step 1 is evenly coated onto the surface of the lithium metal negative electrode sheet with a glass scraper preheated at 80°C, and the scraper gap is controlled at 10 µm. Step 3: After coating, place the lithium metal negative electrode sheet coated with molten Li(FSA)(SN)2 liquid on the surface of the heating table and heat and keep it at 80°C for 5 minutes to completely melt the molecular crystal Li(FSA)(SN)2 and spread it evenly on the surface of the lithium metal negative electrode sheet to form a dense liquid film. Step 4: Cool the temperature to room temperature to allow the liquid film to cool and solidify on the surface of the lithium metal anode, forming a continuous and dense Li(FSA)(SN)2 molecular crystal protective layer. The resulting lithium anode is a lithium metal anode with a self-healing molecular crystal protective layer, named Li@Li(FSA)(SN)2.

[0055] The resulting lithium metal anode sheet with a self-healing molecular crystal protective layer is as follows: Figure 2 As shown, it is named Li@Li(FSA)(SN)2. Its SEM cross-sectional morphology is as follows. Figure 3 As shown, it can be observed that the Li(FSA)(SN)2 protective layer is tightly bonded to lithium metal, the protective layer is dense without obvious gaps, and the thickness of the protective layer is about 5 µm.

[0056] Local pressure was artificially applied to the Li@Li(FSA)(SN)2 sample prepared in step 4, and cracks were observed in the protective layer on the lithium metal surface. The cracked Li@Li(FSA)(SN)2 sample was then placed back on the heating plate and heated at 80°C for 5 minutes. It was observed that the molten material at the cracks re-flowed and healed, and a complete film was formed after cooling.

[0057] like Figure 4 As shown, after being heated and melted, the local cracks that were originally caused by mechanical damage were repaired.

[0058] This embodiment provides a method for assembling a symmetric battery based on molecular crystal materials, including the following steps: The colorless and transparent molten Li(FSA)(SN)2 liquid obtained in step 1 was allowed to stand at room temperature to obtain molecular crystal Li(FSA)(SN)2 powder; 50 mg of molecular crystal Li(FSA)(SN)2 powder was taken and pressed into a tablet (400 MPa, 30 s), and stainless steel gaskets SS with a diameter of 10 mm were placed on both sides. A pressure of 100 MPa was applied and held for 10 s to assemble a symmetrical cell SS / Li(FSA)(SN)2 / SS.

[0059] This embodiment provides a method for assembling a symmetrical battery with a lithium metal anode having a molecular crystal protective layer, including the following steps: Take 120 mg of Li6PS5Cl (LPSC) sulfide solid electrolyte powder, place it in a polytetrafluoroethylene sleeve with an inner diameter of 10 mm, apply a pressure of 400 MPa, and hold for 30 s to obtain a solid electrolyte sheet. Use the Li@Li(FSA)(SN)2 sample prepared in step 4 as the two electrodes of the symmetric cell, place them on both sides of the solid electrolyte sheet, and press them together at 50 MPa for 30 seconds to assemble the symmetric cell.

[0060] This embodiment provides a method for assembling an all-solid-state lithium battery with a lithium metal anode sheet having a self-healing molecular crystal protective layer, including the following steps: Step 5: According to the mass ratio, mix Li6PS5Cl (LPSC) sulfide solid electrolyte powder and LiNi 0.7 Co 0.1 Mn 0.2 O2 (NCM712) positive electrode active material and vapor-grown carbon fiber (VGCF) were placed in a planetary ball mill at a ratio of 28:70:2, with a ball-to-material ratio of 8:1, a rotation speed of 30 rpm, and a time of 20 min to prepare composite positive electrode powder. Step 6: In a polytetrafluoroethylene mold with an inner diameter of 10 mm, 120 mg of LPSC sulfide solid electrolyte powder and 15 mg of composite cathode powder are added sequentially, and the mixture is pressed at 300 MPa to form the solid electrolyte. Then, the Li@Li(FSA)(SN)2 sample prepared in step 4 is placed on the exposed side of the LPSC sulfide solid electrolyte with the molecular crystal protective layer facing the LPSC sulfide solid electrolyte. A pressure of 50 MPa is applied and maintained for 30 s to complete the assembly of the all-solid-state lithium battery.

[0061] Example 2 A method for preparing a lithium metal anode sheet with a self-healing molecular crystal protective layer includes the following steps: Step 1: In a nitrogen-filled glove box (with water and oxygen content both below 0.1 ppm), weigh the dried lithium bis(fluorosulfonyl)imide (LiFSA, 5.04 mmol, 0.9428 g) and succinate (SN, 10.0 mmol, 0.8024 g), add them to the reaction flask, seal it, transfer it to a heating platform, heat it to 60°C and stir it at a constant temperature until all solids are completely melted to form a colorless and transparent molten Li(FSA)(SN)2 liquid; Step 2: In a nitrogen glove box, take a lithium sheet with a thickness of 100 µm, gently wipe the surface with a non-woven cloth, and spread it evenly on the surface of a glass plate. The infrared lamp heating temperature is controlled at 60°C. The molten Li(FSA)(SN)2 liquid obtained in Step 1 is dripped onto the surface of the lithium metal negative electrode sheet using a dropper. Step 3: After coating, the lithium metal anode sheet coated with molten Li(FSA)(SN)2 liquid is heated and kept warm under an infrared lamp for 30 minutes at a temperature of 60°C, so that the molecular crystal Li(FSA)(SN)2 is completely melted and further spread evenly on the surface of the lithium metal anode sheet to form a dense liquid film. Step 4: Cool the temperature to room temperature to allow the liquid film to cool and solidify on the surface of the lithium metal anode, forming a continuous and dense Li(FSA)(SN)2 molecular crystal protective layer. The resulting lithium anode is a lithium metal anode with a self-healing molecular crystal protective layer, named Li@Li(FSA)(SN)2.

[0062] The thickness of the obtained molecular crystal protective layer is approximately 5 µm, as determined by SEM cross-sectional analysis.

[0063] Local pressure was artificially applied to the Li@Li(FSA)(SN)2 sample prepared in step 4, and cracks were observed in the protective layer on the lithium metal surface. The composite lithium metal anode with the cracked protective layer was placed back on the heating plate and heated at 80°C for 5 minutes. It was observed that the molten material at the crack reflowed and healed, and a complete film was formed after cooling.

[0064] This embodiment provides a method for assembling an all-solid-state lithium battery with a lithium metal anode sheet having a self-healing molecular crystal protective layer, including the following steps: Step 5: According to the mass ratio, Li3InCl6 halide solid electrolyte powder, LiFePO4 positive electrode active material and carbon nanotubes (CNTs) are put into a planetary ball mill in a ratio of 18:80:2, with a ball-to-material ratio of 8:1, a rotation speed of 30 rpm and a time of 20 min to prepare composite positive electrode powder. Step 6: In a polytetrafluoroethylene mold with an inner diameter of 10 mm, 120 mg of Li3InCl6 halide solid electrolyte powder and 15 mg of composite cathode powder are added sequentially, and the mold is formed under pressure of 300 MPa. Then, the Li@Li(FSA)(SN)2 sample prepared in step 4 is placed on the exposed side of the Li3InCl6 halide solid electrolyte, with the molecular crystal protective layer facing the Li3InCl6 halide solid electrolyte, and a pressure of 50 MPa is applied for 30 s to complete the assembly of the all-solid-state lithium battery.

[0065] Example 3 A method for preparing a lithium metal anode sheet with a self-healing molecular crystal protective layer includes the following steps: Step 1: In a nitrogen-filled glove box (with water and oxygen content both below 0.1 ppm), weigh the dried lithium bis(fluorosulfonyl)imide (LiFSA, 5.04 mmol, 0.9428 g) and succinate (SN, 10.0 mmol, 0.8024 g), add them to the reaction flask, seal it, transfer it to a heating platform, heat it to 70°C and stir it at a constant temperature until all the solids are completely melted to form a colorless and transparent molten Li(FSA)(SN)2 liquid; Step 2: In a nitrogen glove box, take a 20 µm thick lithium thin film metal anode containing copper foil current collector, gently wipe the surface with non-woven cloth, and place it in an oven. The heating temperature is controlled at 70°C. Immerse the surface of the lithium thin film metal anode in the molten Li(FSA)(SN)2 liquid obtained in step 1 to achieve coating of the lithium thin film metal anode surface. Step 3: After coating, the lithium thin film metal anode sheet coated with molten Li(FSA)(SN)2 liquid is placed in an oven and heated and kept warm for 15 minutes at a temperature of 70°C to completely melt the molecular crystal Li(FSA)(SN)2 and further spread it evenly on the surface of the lithium thin film anode sheet to form a dense liquid film. Step 4: Cool the temperature to room temperature to allow the liquid film to cool and solidify on the surface of the lithium metal anode, forming a continuous and dense Li(FSA)(SN)2 molecular crystal protective layer. The resulting lithium anode is a lithium metal anode with a self-healing molecular crystal protective layer, named Li@Li(FSA)(SN)2.

[0066] The thickness of the obtained molecular crystal protective layer is approximately 8 µm, as determined by SEM cross-sectional analysis.

[0067] Local pressure was artificially applied to the Li@Li(FSA)(SN)2 sample prepared in step 4, and cracks were observed in the protective layer on the lithium metal surface. The composite lithium metal anode with the cracked protective layer was placed back on the heating plate and heated at 80°C for 5 minutes. It was observed that the molten material at the crack reflowed and healed, and a complete film was formed after cooling.

[0068] This embodiment provides a method for assembling an all-solid-state lithium battery with a lithium metal anode sheet having a self-healing molecular crystal protective layer, including the following steps: Step 5, according to the mass ratio, add Li 10 GeP2S 12 (LGPS) solid electrolyte powder, lithium-rich manganese-based cathode active material Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O2 (i.e., 0.5Li2MnO3) 0.5LiNi 0.325 Co 0.325 Mn 0.35 O2 and Ketjen black were added to a planetary ball mill in a ratio of 38:60:2, with a ball-to-material ratio of 8:1, a rotation speed of 30 rpm, and a time of 20 min to prepare composite cathode powder. Step 6: In a polytetrafluoroethylene mold with an inner diameter of 10 mm, 120 mg of LGPS solid electrolyte powder and 15 mg of composite cathode powder were added sequentially, and the mixture was molded under pressure of 300 MPa. Subsequently, the Li@Li(FSA)(SN)2 sample prepared in Step 4 was placed in a Li 10 GeP2S 12 (LGPS) On the exposed side of the solid electrolyte, the molecular crystal protective layer faces Li. 10 GeP2S 12 (LGPS) solid electrolyte, apply 50 MPa pressure and maintain for 30 s to complete the assembly of all-solid-state lithium battery.

[0069] Example 4 A method for preparing a lithium metal anode sheet with a self-healing molecular crystal protective layer includes the following steps: Step 1: In a glove box filled with argon (water and oxygen content both below 0.1 ppm), weigh the dried lithium bis(fluorosulfonyl)imide (LiFSA, 5.04 mmol, 0.9428 g) and succinate (SN, 10.0 mmol, 0.8024 g), add them to the reaction flask, seal it, transfer it to a heating platform, heat it to 75°C and stir it at a constant temperature until all solids are completely melted to form a colorless and transparent molten Li(FSA)(SN)2 liquid; Step 2: In an argon glove box (where water and oxygen content are both below 0.1 ppm), take a lithium sheet with a thickness of 100 µm, gently wipe the surface with a non-woven cloth, and spread it evenly on the surface of a glass plate. The infrared lamp heating temperature is controlled at 75°C. The molten Li(FSA)(SN)2 liquid obtained in Step 1 is dripped onto the surface of the lithium metal negative electrode sheet using a dropper. Step 3: After coating, the lithium metal anode sheet coated with molten Li(FSA)(SN)2 liquid is heated and kept warm under an infrared lamp for 10 minutes at a temperature of 75°C, so that the molecular crystal Li(FSA)(SN)2 is completely melted and further spread evenly on the surface of the lithium metal anode sheet to form a dense liquid film. Step 4: Cool the temperature to room temperature to allow the liquid film to cool and solidify on the surface of the lithium metal anode, forming a continuous and dense Li(FSA)(SN)2 molecular crystal protective layer. The resulting lithium anode is a lithium metal anode with a self-healing molecular crystal protective layer, named Li@Li(FSA)(SN)2.

[0070] The thickness of the obtained molecular crystal protective layer is approximately 10 µm, as determined by SEM cross-sectional analysis.

[0071] Local pressure was artificially applied to the Li@Li(FSA)(SN)2 sample prepared in step 4, and cracks were observed in the protective layer on the lithium metal surface. The composite lithium metal anode with the cracked protective layer was placed back on the heating plate and heated at 80°C for 5 minutes. It was observed that the molten material at the crack reflowed and healed, and a complete film was formed after cooling.

[0072] This embodiment provides a method for assembling an all-solid-state lithium battery with a lithium metal anode sheet having a self-healing molecular crystal protective layer, including the following steps: Step 5: According to the mass ratio, add Li7P3S 11 (i.e., 70Li2S-30P2S5) solid electrolyte powder, lithium cobalt oxide (LiCoO2) positive electrode active material and Ketjen black were put into a planetary ball mill in a ratio of 28:70:2, with a ball-to-material ratio of 8:1, a rotation speed of 30 rpm and a time of 20 min to prepare composite positive electrode powder. Step 6: Add 120 mg of Li7P3S sequentially into a polytetrafluoroethylene mold with an inner diameter of 10 mm. 11 Solid electrolyte powder and 15 mg of composite cathode powder were molded under pressure of 300 MPa. Subsequently, the Li@Li(FSA)(SN)2 sample prepared in step 4 was placed in Li7P3S 11 On the exposed side of the solid electrolyte, the molecular crystal protective layer faces Li7P3S. 11 Solid electrolyte, apply 50MPa pressure and maintain for 30 s to complete the assembly of all-solid-state lithium battery.

[0073] Comparative Example 1 In an argon glove box (with water and oxygen content below 0.1 ppm), 120 mg of Li6PS5Cl solid electrolyte powder was pressed into a tablet at 400 MPa for 30 s. Then, uncoated lithium metal negative electrode sheets were placed on both sides of the electrolyte as the two electrodes of the symmetrical cell, and the symmetrical cell was assembled by pressing at 50 MPa for 30 s.

[0074] Comparative Example 2 Step 1: In an argon glove box (water and oxygen content both below 0.1 ppm), Li6PS5Cl (LPSC) sulfide solid electrolyte powder and LiNi were added according to the mass ratio. 0.7 Co 0.1 Mn 0.2 O2 (NCM712) positive electrode active material and vapor-grown carbon fiber (VGCF) were placed in a planetary ball mill at a ratio of 28:70:2, with a ball-to-material ratio of 8:1, a rotation speed of 30 rpm, and a time of 20 min to prepare composite positive electrode powder. Step 2: In a 10 mm inner diameter polytetrafluoroethylene mold, 120 mg of LPSC sulfide solid electrolyte powder and 15 mg of composite cathode powder are added sequentially, and the mixture is molded under pressure of 300 MPa. Subsequently, the uncoated lithium metal anode sheet is placed on the exposed side of the LPSC sulfide solid electrolyte, and a pressure of 50 MPa is applied and maintained for 30 s to complete the assembly of the all-solid-state lithium battery.

[0075] Comparative Example 3 Step 1: In an argon glove box (with water and oxygen content both below 0.1 ppm), Li3InCl6 halide solid electrolyte powder, LiFePO4 positive electrode active material, and carbon nanotubes (CNTs) are placed into a planetary ball mill at a mass ratio of 18:80:2, with a ball-to-material ratio of 8:1, a rotation speed of 30 rpm, and a time of 20 min to prepare composite positive electrode powder. Step 2: In a polytetrafluoroethylene mold with an inner diameter of 10 mm, 120 mg of Li3InCl6 solid electrolyte powder and 15 mg of composite positive electrode powder are added sequentially, and the mold is formed under pressure of 300 MPa. Subsequently, the uncoated lithium metal negative electrode sheet is placed on the exposed side of the Li3InCl6 solid electrolyte, and a pressure of 50 MPa is applied and maintained for 30 s to complete the assembly of the all-solid-state lithium battery.

[0076] Comparative Example 4 Step 1: In an argon glove box (water and oxygen content both below 0.1 ppm), LGPS solid electrolyte powder and Li... (The sentence is incomplete and requires more context to translate accurately). 1.2 Mn 0.54 Ni 0.13 Co 0.13 O2 positive electrode active material and Ketjen black were put into a planetary ball mill in a ratio of 38:60:2, with a ball-to-material ratio of 8:1, a rotation speed of 30 rpm, and a time of 20 min to prepare composite positive electrode powder. Step 2: In a 10 mm inner diameter polytetrafluoroethylene mold, 120 mg of LGPS solid electrolyte powder and 15 mg of composite positive electrode powder are added sequentially, and the mixture is molded under pressure of 300 MPa. Subsequently, the uncoated lithium metal negative electrode sheet is placed on the exposed side of the LGPS solid electrolyte, and a pressure of 50 MPa is applied and maintained for 30 s to complete the assembly of the all-solid-state lithium battery.

[0077] Performance testing The SS / Li(FSA)(SN)2 / SS symmetrical cell assembled in Example 1 was subjected to AC impedance testing (frequency range 1 Hz to 1 MHz) at different temperatures (10°C, 20°C, 30°C, 40°C, 50°C). The measured Nyquist plots of the symmetrical cell are shown below. Figure 5 As shown in (a), the calculated lithium-ion conductivity using the R value is 3.49 × 10⁻⁶. -5 S cm -1 3.98×10 -5 S cm -1 5.66×10 -5 S cm -1 8.9×10 -5 S cm -1 and 1.1×10 -4 S cm -1 Therefore, the Arrhenius curve is plotted (e.g., Figure 5 As shown in (b) of the figure, the corresponding activation energy is 10.19 kJ mol. -1 .

[0078] The symmetrical cells of Comparative Example 1 and Example 1 were subjected to critical current density (CCD) tests at room temperature. The test results are as follows: Figure 6 As shown, the symmetric cell with a Li(FSA)(SN)2 protective layer in Example 1 exhibits a high efficiency of 3.1 mA cm⁻¹. -2 CCD value (e.g.) Figure 6 As shown in (a), it is significantly higher than 1 mA cm⁻¹ in Comparative Example 1. -2 (like Figure 6 As shown in (b) of the paper, the molecular crystal protective layer of the present invention can effectively suppress lithium dendrite growth and improve interface stability.

[0079] The all-solid-state batteries of Comparative Example 1 and Example 1 were subjected to constant current charge-discharge cycle tests. The tests were conducted at room temperature with a current density of 0.2 mA cm⁻¹. -2 The cutoff capacity is 0.2 mAh cm⁻¹. -2 The test results are as follows: Figure 7As shown, the symmetric battery with a Li(FSA)(SN)2 molecular crystal protective layer in Example 1 exhibits excellent cycle stability at 0.2 mA cm⁻¹. -2 After more than 200 hours of stable cycling, the polarization voltage remained at a low level (<20 mV). In contrast, the symmetric cell without a molecular crystal protective layer in Comparative Example 1 experienced a sudden increase in polarization voltage to over 30 mV after about 50 hours of cycling, accompanied by a sharp voltage drop caused by a micro-short circuit. After the drastic fluctuations, it failed due to a short circuit.

[0080] The all-solid-state batteries of Comparative Example 2 and Example 1 were subjected to a 0.5C constant current charge-discharge cycle test at 25°C, with a voltage range of 2.5~4.2 V (pre-cycled at 0.2C for 2 cycles, 1C = 200 mA g). -1 The result is as follows: Figure 8 As shown, the battery employing the molecular crystal protective layer of this invention has an initial discharge capacity of 139.6 mAh g⁻¹ at 0.5C. -1 After 240 cycles, the capacity retention was 71.5%, with an average coulombic efficiency exceeding 99%; while the control battery using bare lithium exhibited an initial capacity of 131.9 mAh g⁻¹ at 0.5C. -1 After 120 cycles, the capacity rapidly decreased to 57.3% of the initial value, and the coulombic efficiency fluctuated significantly. This indicates that the Li(FSA)(SN)2 protective layer effectively suppressed interfacial side reactions and lithium dendrite growth, significantly improving the battery cycle life.

[0081] The all-solid-state battery assembled in Example 1 was subjected to a 0.5C constant current charge-discharge cycle test, with a voltage range of 2.5~4.2V. After 50 cycles, the battery underwent an AC impedance test. After the test, the battery was placed at 80°C for 10 minutes for thermal repair treatment, and an AC impedance test was performed afterward. The test results are as follows. Figure 9 As shown, the interface impedance (EIS semicircle) of the battery is significantly reduced after repair, proving that the protective layer of the present invention has excellent thermal repair capability.

[0082] The all-solid-state batteries assembled in Example 2 and Comparative Example 3 were subjected to a 0.5C constant current charge-discharge cycle test at 25°C, with a voltage range of 2.0~3.8 V (1C = 170 mA·g). -1 Test results show that the battery using the molecular crystal protective layer of this invention has an initial discharge capacity of 138.5 mAh·g at 0.5C. -1 After 200 cycles, the capacity retention was 76.8%, and the average coulombic efficiency was above 99.2%, demonstrating excellent interface stability. The battery in Comparative Example 3 had an initial discharge capacity of 110.3 mAh·g at 0.5C. -1After about 100 cycles, the capacity decreased sharply to 43.2% of the initial value. The coulombic efficiency fluctuated significantly and dropped rapidly, indicating that the side reactions at the interface between bare lithium and halide electrolyte were severe, leading to rapid battery failure.

[0083] The all-solid-state batteries assembled in Example 3 and Comparative Example 4 were subjected to a 0.2C constant current charge-discharge cycle test at 25°C, with a voltage range of 2.0~4.8 V (1C = 250 mA·g). -1 Test results show that the initial discharge capacity of the battery using the molecular crystal protective layer of this invention is 242.5 mAh·g. -1 After 150 cycles, the capacity retention was 71.5%, and the average coulombic efficiency was higher than 98.6%, demonstrating the effectiveness of the protective layer of this invention in different battery systems. Comparative Example 4 battery had an initial discharge capacity of 186.8 mAh·g at 0.2C. -1 After about 100 cycles, the capacity decayed to 48.7% of the initial value, and the charge / discharge polarization voltage continued to increase, indicating that the interface between bare lithium and LGPS solid electrolyte was unstable and the continuous increase in impedance led to rapid degradation of battery performance.

Claims

1. A lithium metal anode sheet with a self-healing molecular crystal protective layer, characterized in that, The molecular crystal protective layer is attached to the surface of the lithium metal negative electrode sheet. The material is lithium bis(fluorosulfonyl)imide-succinate organic molecular crystal with the chemical formula Li{N(SO2F)2}-(NCCH2CH2CN)2.

2. A method for preparing a lithium metal anode sheet with a self-healing molecular crystal protective layer, characterized in that, Includes the following steps: Step 1: Under an inert atmosphere, lithium bis(fluorosulfonyl)imide (LiFSA) and succinate (SN) raw materials mixed in a molar ratio of 1:2 are heated and stirred at 60-80°C to form a colorless and transparent molten Li(FSA)(SN)2 liquid. Step 2: Spread the lithium metal anode sheet evenly and heat it. Control the heating temperature at 60-80°C. Coat the surface of the heated lithium metal anode sheet with the molten Li(FSA)(SN)2 liquid obtained in Step 1 evenly. Step 3: Heat and hold the lithium metal anode sheet coated with molten Li(FSA)(SN)2 liquid for 5 to 30 minutes to completely melt the molecular crystal Li(FSA)(SN)2 and further spread it evenly on the surface of the lithium metal anode sheet to form a dense liquid film. Step 4: Cool the temperature to room temperature to allow the liquid film to cool and solidify on the surface of the lithium metal anode sheet, forming a continuous and dense Li(FSA)(SN)2 molecular crystal protective layer, thus obtaining a lithium metal anode sheet with a self-healing molecular crystal protective layer.

3. The method for preparing a lithium metal anode sheet with a self-healing molecular crystal protective layer according to claim 2, characterized in that, In step 2, the coating method includes any one of drip coating, scraping coating or immersion coating. The amount of Li(FSA)(SN)2 molten liquid is calculated according to the target thickness. The thickness of the molecular crystal protective layer after coating is controlled at 5~10 µm. The lithium metal negative electrode sheet is in the shape of a lithium foil, a lithium sheet, or a lithium film deposited on a current collector.

4. The method for preparing a lithium metal anode sheet with a self-healing molecular crystal protective layer according to claim 2, characterized in that, In step 3, the heating and heat preservation temperature is 60-80°C; In step 2 or 3, the heating method is hot plate heating, oven heating or infrared heating; wherein, hot plate heating uses a small constant temperature heating table, and infrared heating uses infrared lamps.

5. The method for preparing a lithium metal anode sheet with a self-healing molecular crystal protective layer according to claim 2, characterized in that, When the lithium metal negative electrode sheet with the self-healing molecular crystal protective layer is subjected to external pressure and local cracks appear, the negative electrode sheet is subjected to short-term heating treatment at 80°C to remelt the failed protective layer and allow it to penetrate into the crack again. After cooling, the interface self-healing is achieved.

6. The application of a lithium metal anode sheet with a self-healing molecular crystal protective layer as described in claim 1, or a lithium metal anode sheet with a self-healing molecular crystal protective layer prepared by the preparation method as described in claims 2-5, in an all-solid-state lithium metal battery, characterized in that, The all-solid-state lithium metal battery includes a positive electrode active material, a solid electrolyte powder, and a lithium metal negative electrode sheet with a self-healing molecular crystal protective layer as described above. The assembly steps of the all-solid-state lithium metal battery include: Step 5: Mechanically mix the positive electrode active material, solid electrolyte powder and conductive agent in a certain proportion to prepare composite positive electrode powder; Step 6: Stack the composite positive electrode powder, solid electrolyte powder, and lithium metal negative electrode sheet with a self-healing molecular crystal protective layer in sequence, and press them together under an inert atmosphere to obtain an all-solid-state lithium metal battery.

7. The application of the lithium metal anode sheet with a self-healing molecular crystal protective layer according to claim 6 in an all-solid-state lithium metal battery, characterized in that, In step 5, the solid electrolyte is a sulfide solid electrolyte or a halide solid electrolyte. The sulfide solid electrolyte comprises: (1). Glass-type electrolytes xLi₂S-(100-x)P₂S₅ (0<x<100), Li₂S–SiS₂–Li₄MO₄, wherein M is one or more of Si, Ge and P in any ratio; (2). Argyrodite-type electrolytes Li₆PS₅X, Li₇PS₆, Li 5.5 PS 4.5 X 1.5 , wherein X is one or more of Cl, Br and I in any ratio; (3). Lithium sulfide crystalline superionic conductor-type electrolytes Li x M 1-y M' y S₄ (0≤y<1, 2≤x≤5), wherein M is one or more of Sn, Ge and Si in any ratio, and M' is one or more of P, Al, Zn, Ga, Sb and As in any ratio; (4). Lithium germanium phosphorus sulfur-type electrolytes Li 11–x M 2–x P 1+x S 12 (0<x<2), Li₇Ge₃PS 12 , Li 11 AlP₂S 12 , wherein M is one or more of Ge, Sn and Si in any ratio; The halide solid electrolyte comprises: (1) Li2MCl4, wherein M is one or two of Mn or Zn in any proportion; (2) LiMX4, wherein M is one or more of Yb or Al or In in any proportion, and X is one or more of F or Cl or Br or I in any proportion; (3) LiMXCl4, wherein M is one or more of Ta or Nb or Sb or Ti or Zr or Hf or Sn in any proportion, and X is one or more of O or F or Cl in any proportion; (4) Li3MX6, wherein M is one or more of Y or In or Er or Ho or Sc or Sm or Nb or Ga or Bi or Lu or Tm or Dy or Tb in any proportion, and X is one or more of Cl or Br or I in any proportion; (5) Li6MX8, wherein M is one or more of Co or V or Fe in any proportion, and X is one or more of Cl or Br or I in any proportion; (6) Li2MX6, wherein M is one or more of Zr or Ti or Sn or Ge in any proportion, and X is one or more of Cl or Br or I in any proportion.

8. The application of the lithium metal anode sheet with a self-healing molecular crystal protective layer according to claim 6 in an all-solid-state lithium metal battery, characterized in that, In step 5, the positive electrode active material is selected from lithium cobalt oxide (LiCoO2), lithium nickel oxide (LiNiO2), lithium manganese oxide (LiMnO2), and lithium nickel manganese cobalt oxide (LiNiO2). 1-x-y Co x Mn y O2, 0 < 1 - xy ≤ 1), lithium nickel cobalt aluminum oxide (LiNi 1-x-y Co x Al y O2, 0 < 1 - xy ≤ 1), LiNi 0.5 Mn 1.5 O4, LiMn2O4, lithium-rich manganese-based cathode (xLi2MnO3·(1-x)LiMO2, where M is one or more of Mn, Co, or Ni in any proportion, 0<1-x≤1), and lithium iron phosphate (LiFePO4) in any proportion; In step 5, the conductive agent is one or more of Ketjen Black, acetylene black, vapor-grown carbon fiber (VGCF), and carbon nanotubes (CNT) in any proportion.

9. The application of the lithium metal anode sheet with a self-healing molecular crystal protective layer according to claim 6 in an all-solid-state lithium metal battery, characterized in that, In step 5, the mass ratio of the positive electrode active material, solid electrolyte powder and conductive agent is (60–80):(38–18):

2.

10. The application of the lithium metal anode sheet with a self-healing molecular crystal protective layer according to claim 6 in an all-solid-state lithium metal battery, characterized in that, In step 6, the pressure for tablet assembly is 50~500 MPa, and the holding time is 10~60 seconds.

Citation Information

Patent Citations

  • A metal lithium anode protected by an artificial solid electrolyte interface layer, and a preparation method and application thereof

    CN109167063A

  • Modified solid electrolyte as well as preparation method and application thereof

    CN113140785A